Phase II and Biomarker Study of Cabozantinib in Metastatic Triple‐Negative Breast Cancer Patients. (17th January 2017) - Tolaney, Sara M.; Ziehr, David R.; Guo, Hao; Ng, Mei R.; Barry, William T.; Higgins, Michaela J.; Isakoff, Steven J.; Brock, Jane E.; Ivanova, Elena V.; Paweletz, Cloud P.; Demeo, Michelle K.; Ramaiya, Nikhil H.; et al.
Abstract : Currently, no targeted therapies are available for metastatic triplenegative breast cancer (mTNBC). We evaluated the safety, efficacy, and biomarkers of response to cabozantinib, a multikinase inhibitor, in patients with mTNBC. We conducted a single arm phase II and biomarker study that enrolled patients with measurable mTNBC. Patients received cabozantinib (60 mg daily) on a 3‐week cycle and were restaged after 6 weeks and then every 9 weeks. The primary endpoint was objective response rate. Predefined secondary endpoints included progression‐free survival (PFS), toxicity, and tissue and blood circulating cell and protein biomarkers. Of 35 patients who initiated protocol therapy, 3 (9% [95% confidence interval (CI): 2, 26]) achieved a partial response (PR). Nine patients achieved stable disease (SD) for at least 15 weeks, and thus the clinical benefit rate (PR+SD) was 34% [95% CI: 19, 52]. Median PFS was 2.0 months [95% CI: 1.3, 3.3]. The most common toxicities were fatigue, diarrhea, mucositis, and palmar‐plantar erythrodysesthesia. There were no grade 4 toxicities, but 12 patients (34%) required dose reduction. Two patients had TNBCs with MET amplification. During cabozantinib therapy, there were significant and durable increases in plasma placental growth factor, vascular endothelial growth factor (VEGF), VEGF‐D, stromal cell‐derived factor 1a, and carbonic anhydrase IX, and circulating CD3 + cells and CD8 + T lymphocytes, and decreases in plasma soluble VEGF receptor 2 and CD14+ monocytes (all p  < .05). Higher baseline concentrations of soluble MET (sMET) associated with longer PFS ( p  = .03). In conclusion, cabozantinib showed encouraging safety and efficacy signals but did not meet the primary endpoint in pretreated mTNBC. Exploratory analyses of circulating biomarkers showed that cabozantinib induces systemic changes consistent with activation of the immune system and antiangiogenic activity, and that sMET should be further evaluated a potential biomarker of response. Abstract : This study evaluates the safety, efficacy, and biomarkers of response to cabozantinib, a multikinase inhibitor, in patients with metastatic triple‐negative breast cancer (mTNBC). Cabozantinib showed encouraging safety and efficacy signals but did not meet the prespecified primary endpoint in pretreated mTNBC. Exploratory analyses of circulating biomarkers showed that cabozantinib induces systemic changes consistent with activation of the immune system and antiangiogenic activity, and soluble MET should be further evaluated as a potential biomarker of response.